Comparative overview of natural and cultural components of the marketing environment for tourism in Kazakhstan and Slovakia - Dorokhov, Oleksandr; Kultan, Jaroslav; Mukhammedov, Abu; Dorokhova, Luidmyla; Malyi, Volodymyr (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Despite the current catastrophic reduction of tourism services and related services in the world in a pandemic, the development of tourism in the long run remains very relevant, especially in anticipation of the reformatting of the global tourism market as one of the results of the end of the pandemic. At the same time, along with the traditional world centers of tourism, we can assume the emergence of new regional and global countries, leaders in tourism. The forthcoming restart of the market will provide a good, rare opportunity for new tourist destinations to express themselves, intensify the attraction of tourists and take certain positions in the resetting tourist market. Therefore, working out their potential and realizing their competitive marketing advantages is important for such tourism-developing countries. Accordingly, this study is devoted to the development of the tourism industry, in particular, the description and analysis of natural conditions and relevant opportunities for the development of health, sports, educational tourism in the Slovak Republic and the Republic of Kazakhstan. A detailed comparative analysis of socio-cultural and natural-geographical components of the marketing environment for the development of tourism in both countries is given. Such popular and demanded in international tourism areas as mountain and skiing, cultural-historical and cognitive, medical and health-improving, as well as recreational tourism are considered in detail. In general, the countries in question have much in common regarding the diverse opportunities and types of tourism. However, due to a number of historical, geographical, socio-social reasons, the level of development of tourist services in them is very different. This study also compares opportunities for the development of relevant tourism in Slovakia and Kazakhstan. In order to present tourism for foreign tourists and create a positive image of Slovakia and Kazakhstan as favorable countries for inbound tourism, it is necessary to actively use modern information technologies and innovations. This article presents such sources of information about tourism potential as websites, links to Internet resources of travel agencies and operators, the main video resources about tourism opportunities in the Republic of Kazakhstan. The development of these innovations will allow the Republic of Kazakhstan to become one of the most competitive countries in the tourist service and become a new significant world tourist center.